Pengaruh Kerjasama, Komunikasi Dan Budaya Organisasi Terhadap Prestasi Kerja Karyawan BUMN PT. Pegadaian Sumbawa Besar - Alma Damayani; I Made Murjana; Syaiful Amri (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to determine the influence of cooperation, communication and organizational culture on the work performance of BUMN PT employees. Sumbawa Besar Pawn Shop. PT. Sumbawa Besar Pawnshop is one of the financial institutions that is widely used by the people of Sumbawa Besar, so the performance of its employees needs to be a concern. This research uses associative research with a population and sample of 40 employees of BUMN PT. Sumbawa Besar Pawn Shop. The data collection technique used in this research is a statement in the form of a questionnaire. Hypothesis testing is partially carried out by the T test and simultaneously by the F test. The results of the research show that there is an influence between cooperation, communication and organizational culture on the work performance of BUMN PT employees. Sumbawa Besar Pawn Shop. Based on data analysis, it shows (1) collaboration has a significant effect on work performance, with a calculated T value of 3.278 which is greater than the T table of 0.028 with a significance of 0.002 which is smaller than 0.05. (2) communication has no significant effect on work performance with a calculated T value of -1.628 which is smaller than the T table of 0.028 with a significance of 0.112 which is greater than 0.05. (3) organizational culture has a significant effect on work performance with a calculated T value of 8.545 which is greater than the T table of 0.028 with a significance of 0.000 which is smaller than 0.05. Then cooperation, communication and organizational culture have a significant effect on the work performance of Pt. employees. Pegadaian Sumbawa Besar with a calculated f value of 255.824 is greater than the f table, namely 2.87 with a significance level of 0.000 which is smaller than 0.05